Struktur Anatomi dan Uji Histokimia Terpenoid dan Fenol Dua Varietas Sirih Hijau (Piper betle L.) - Gusti Puspa Dewi; Evi Mintowati Kuntorini; Eny Dwi Pujawati (Bioscientiae, 2020)
This study aims to determine the anatomical structure and histochemical test of terpenoid and phenol compounds in two varieties of green betel plants (Piper betle). Making leaves anatomical structure preparations using the fresh method, testing terpenoid compounds with 5% copper acetate, testing phenol with ferric trichloride 10% and some grains of sodium carbonate. The observations of the anatomical structure of green betel leaf varieties 1 and varieties 2 have similarities consisting of the upper epidermis, upper hypodermis, palisade parenchyma, parenchymal sponges, vascular bundles (xylem and phloem), sclerenchyma, cholenchyma, lower epidermis, lower hypodermis, secretory cells, trichoma, stoma and calcium oxalate crystals, and in varieties 2 look more trichomes. The anatomical structure of the variety 1 betel stem and varieties 2 are arranged from the outside in the direction of the epidermal tissue, colenchymal tissue, cortical bundles, sclerenchyma, cortex, medullary and peripheral vascular files, pith, the central part of the stem is a secretory gland. Phenol in betel vine varieties 1 and varieties 2 is positive in the secretion cell part which is spread in the parenchymal tissue of the mother's leaf bone and lamina, whereas in the stem is spread around the cortex and pith parenchyma. Positive secretion cells contain phenol not as much as secretory cells containing terpenoids. Based on quantitative observations the size of oil cell density and secretion cell diameter, the essential oils contained in the cell secretions in the leaves of variety 1 are more than varieties 2 while in the varieties 2, there are more varieties 1.